1995
DOI: 10.1063/1.469966
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectrum and excitation profile of mass-selected zirconium trimers

Abstract: We present the resonance Raman and Raman excitation profile of mass-selected zirconium trimers in argon matrices. In the Raman spectra, two fundamentals and one overtone are observed. Average Raman shifts, along with standard deviations (in parentheses) are 176.7 (13) cm−1 (ν2), 258.0 (12) cm−1 (ν1), and 516.1 (8) cm−1 (2ν1). The ratio of the frequencies of the two lowest lines (ν1/ν2) is 1.46, which is very close to √2. This is indicative of a symmetrical equilateral geometry (D3h). In such a case we expect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 10 publications
3
14
0
2
Order By: Relevance
“…The most stable structure was found to be the equilateral triangle with D 3h symmetry which is in agreement with the experimental results [9]. Previous study [15] using the CAS-MCSCF method predicted that the most stable structure for Zr 3 is the C 2v symmetry with…”
supporting
confidence: 91%
“…The most stable structure was found to be the equilateral triangle with D 3h symmetry which is in agreement with the experimental results [9]. Previous study [15] using the CAS-MCSCF method predicted that the most stable structure for Zr 3 is the C 2v symmetry with…”
supporting
confidence: 91%
“…3 and with each other. 5 mode is the totally symmetric stretching of the Nb-Nb bonds. The 6 and 7 modes are deformation of the Nb 3 triangle.…”
Section: Spectral Analysis and Discussionmentioning
confidence: 99%
“…The f n ( f 0, , f 1 , f 2 , f 3 ) bands have energies of 0Ϫ0 ϩ339 cm Ϫ1 ϩ258n cm Ϫ1 , suggesting that they are combination bands of 5 ϩ ϩn 6,7 ϩ (6 0 p 7 9 nϪp 5 0 1 ). This gives a frequency of 339 cm Ϫ1 for the ion mode 5 ϩ . The b n , d n , and g n progressions appear to be due to transitions from the excited vibrational level of a neutral mode with its frequency being 20 cm Ϫ1 smaller than that of the ion.…”
Section: Spectral Analysis and Discussionmentioning
confidence: 99%
“…of both Zr 3 3 and Nb 3 5 have D 3h symmetry, although in both cases there is little or no vibronic distortion. On the other hand Cu 3 10 is well known to be a fluxional molecule in the ground state and is perhaps the best model for the present case.…”
Section: Discussionmentioning
confidence: 95%
“…Ozin and MacIntosh 6 have suggested that force constants for higher clusters (n Ͼ2) may be obtained from that of the dimer by simple distribution among the various bonds and we have found this to be a reliable guide. 7,8 Assuming a central force field, the totally symmetric fundamental frequency for a trimer should be observed at approximately )/2ϭ0.866 times the dimer frequency. For dihafnium the fundamental frequency is 176 cm Ϫ1 predicting a trimer frequency of 152 cm Ϫ1 , so it is likely that the observed intervals (143-152 cm Ϫ1 ) correspond to the totally symmetric vibration.…”
Section: A Raman Spectramentioning
confidence: 99%